Mesoporous silicon nanoparticles for targeted two-photon theranostics of prostate cancer. Issue 21 (13th May 2016) - Chaix, Arnaud; El Cheikh, Khaled; Bouffard, Elise; Maynadier, Marie; Aggad, Dina; Stojanovic, Vanja; Knezevic, Nikola; Garcia, Marcel; Maillard, Philippe; Morère, Alain; Gary-Bobo, Magali; Raehm, Laurence; et al.
Abstract : Porous silicon nanoparticles grafted with a mannose-6-phosphate analogue were designed for targeting prostate cancer cells. Abstract : A novel non-toxic porous silicon nanoparticle grafted with a mannose-6-phosphate analogue and applicable in 2-photon imaging and photodynamic therapy was specifically designed for targeting prostate cancer cells.